Temperature-based structural health monitoring baseline for long-span bridges. (1st March 2015) - Yarnold, M.T.; Moon, F.L.
Highlights: Developed a 3D temperature-driven baseline for long-span bridge SHM systems. Numerical benchmark studies conducted. Field monitoring study performed on a long-span arch bridge. Numerical simulations conducted for realistic damage scenarios. Results compared with a vibration-driven approach and conclusions drawn. Abstract: A core prerequisite of an effective structural health monitoring (SHM) system is the development and characterization of a baseline response that is sensitive to meaningful changes in the structural system, and insensitive to normal operational changes. Such a baseline allows the use of detected changes to drive proactive maintenance and preservation interventions, or more refined assessment approaches, to ensure the on-going safety, serviceability, and durability of the structure. The approach developed as part of this research utilizes the relationship between temperature changes and the resulting strains and displacements of the structure to create a unique numerical and graphical baseline within an SHM framework. Evaluation of the method was performed through benchmark studies along with long-term monitoring data from a long-span steel tied arch bridge. The benchmark studies and field measurements illustrate that the nonlinear relationship between temperature, local mechanical strains, and global displacements results in a near-flat surface when plotted in 3D space. The bounds and the orientation (angle) of these surfaces are unique for each location and insensitive to normal operational changes in behavior. More importantly, a numerical sensitivity study was performed which indicated the surfaces are sensitive to a series of realistic scenarios which would result in meaningful changes in the performance of the structure. In addition, a comparison with a vibration-based SHM approach was also carried out, and the results indicated that the temperature-based approach was more sensitive for the scenarios examined.